2011
DOI: 10.1111/j.1533-2500.2011.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Neuropathic Cancer Pain: A Comprehensive Review of the Current Literature

Abstract: Neuropathic cancer pain (NCP), commonly encountered in clinical practice, may be cancer-related, namely resulting from nervous system tumor invasion, surgical nerve damage during tumor removal, radiation-induced nerve damage and chemotherapy-related neuropathy, or may be of benign origin, unrelated to cancer. A neuropathic component is evident in about 1/3 of cancer pain cases.Although from a pathophysiological perspective NCP may differ from chronic neuropathic pain (NP), such as noncancer-related pain, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 259 publications
(295 reference statements)
2
84
0
1
Order By: Relevance
“…A greater proportion of patients with PainDETECT end scores of <13 received a diagnosis of neuropathic pain after examination of this questionnaire (36 of 127 [28.3%]) than patients with PainDETECT end scores of >18 (indicative that underlying CRNP was likely) who were considered not to experience neuropathic pain (three of 27 [11.1%]; Table 5). This trend is consistent with the findings of a recent review of pharmacologic treatments for CRNP that identified a shift from a trend of underdiagnosis of CRNP to hyperdiagnosis, explained by the researchers as a potential confusion between symptoms of neuropathic pain and hyperalgesia resulting from opioid administration [27]. Consequently, identifying screening tools that can help physicians characterise and diagnose the nature of pain is paramount to improving pain management in cancer patients, particularly as poor pain assessment has been identified as a contributing factor to the current undertreatment of cancer pain in general [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…A greater proportion of patients with PainDETECT end scores of <13 received a diagnosis of neuropathic pain after examination of this questionnaire (36 of 127 [28.3%]) than patients with PainDETECT end scores of >18 (indicative that underlying CRNP was likely) who were considered not to experience neuropathic pain (three of 27 [11.1%]; Table 5). This trend is consistent with the findings of a recent review of pharmacologic treatments for CRNP that identified a shift from a trend of underdiagnosis of CRNP to hyperdiagnosis, explained by the researchers as a potential confusion between symptoms of neuropathic pain and hyperalgesia resulting from opioid administration [27]. Consequently, identifying screening tools that can help physicians characterise and diagnose the nature of pain is paramount to improving pain management in cancer patients, particularly as poor pain assessment has been identified as a contributing factor to the current undertreatment of cancer pain in general [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…15,16 GBP exert AHA action probably by acting in brain stem thereby causing descending inhibition and anti-allodynic action probably by altering microglial functions. 17 Beneficial effects of AMT in NP are independent of antidepressant action as indicated by requirement of low dose (25-100 mg daily) for analgesic action than antidepressant action. ADRs of AMT are common and around one third patient suffer from mild adverse effects while 8% of the patient stop taking drug due to severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…[119] Recently, it was reported that an anti-PD-L1 antibody, which blocks the PD-1/PD-L1 pathway, can improve macrophage-mediated T cell activation and has progressed to clinical trials. [120] www.wjpr.net …”
Section: -Macrophages As Attractive Targets For Therapeutic Intervenmentioning
confidence: 99%